Wewenang Jaksa Agung dalam Penyampingan Perkara (Deponering) dalam Proses Peradilan Pidana - I Gusti Agung Ngurah Satya Widiana; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Analogi Hukum, 2022)
The existence of a waiver of a case in court or in this case it can be said that Deponering intends to carry out a step aside from a case carried out by the attorney general in a judicial process in court. The existence of an attitude or step that sets aside a case in a court carried out by the attorney general, all these related matters have been contained in RI Law No. 16 of 2004 which is related to the prosecutor's office. The formulation of the problem is . What is the authority of the attorney general in Article 35 c of the Law of the Republic of Indonesia Number 16 of 2004? And What are the legal implications for the regulation of public interest as a condition for the use of Deponering by the Attorney General? The research used in this research is normative law. The duties and powers of the Attorney General can be seen in Article 35 of Law No. 16 of 2004. One of the powers of the Attorney General, namely Article 35 C, is to set aside cases in the public interest.